The Relationship between Awareness and Preventive Practice of COVID-19 and the Intention of Taking Vaccination among Batu Pahat Residents - Chua, Woei Bin; Shahrul Nizam Salahudin (Research in Management of Technology and Business, 2024)
Many other countries had researched how the citizens’ attitudes about the COVID-19 vaccine acceptance or intention. The problem recently was the booster vaccine receive rate was low in Malaysia. This study will identify the level of awareness about COVID-19, the level of preventive practice about COVID-19, and the level of intention to take vaccination, and identify the relationship between these variables among Batu Pahat residents. A close-ended quantitative questionnaire had been developed with Google Forms will be used for gathering the necessary information. A total of 138 respondents contributed to the result of the study. From the descriptive analysis, there is a high level of awareness, poor level of preventive practice, and poor level of intention of taking vaccination. The result shows that one of the hypotheses has achieved at correlation coefficient analysis – Spearman’s rho test, another is rejected. The preventive practice has a positive moderate association with the intention of taking vaccination with significance. Awareness about COVID-19 then no significant connection with the intention of taking vaccination.